External Pay Transparency and the Gender Wage Gap - Wolfgang Frimmel; Bernhard Schmidpeter; Rene Wiesinger; Rudolf Winter-Ebmer (Institute of Labor Economics (IZA), 2023)
We show that providing publicly available wage information in vacancies, so-called external pay transparency, can reduce the gender wage gap. There is an increasing interest in pay transparency policies as a tool to combat unequal pay. We exploit a reform of Austria's Equal Treatment Law to evaluate how providing wage information in vacancies affects the gender wage gap. To take into account that the value of providing such external pay information is likely to be heterogeneous along the wage distribution, we implement a Quantile Difference-in-Difference model. The reform led to a small overall reduction of the gender wage gap. Our main results highlight that reductions in the wage gap are larger in circumstances where women are likely to hold misspecified beliefs about their labor market options and when needing to make job acceptance decisions under pressure. The reduction in the gender wage gap was caused by an increase in women's earnings, particularly at the lower part of the distribution. Earnings of men, on the other side, remained largely constant. Our results lend support to policy proposals aimed at increasing external pay transparency.
Keywords: J31; J23; J23; J63; 330; mandatory wage posting; pay transparency law; gender wage gap; job postings; quantile DiD